Bahasa Inggris - Syarifah Chaniago; Saiful Anwar Matondang; M. Manugeren M. Manugeren (BASIS (Bahasa dan Sastra Inggris), 2026)
This study examines the representation of ideological motherhood and waiting in Lyora by Fenty Effendy. Its significance lies in revealing how maternal trauma is constructed and normalised through literary language within ideological expectations of motherhood. The object of the study is the novel’s representation of motherhood, analysed through a literary stylistics framework informed by trauma theory (Vickroy), feminist motherhood (O’Reilly), and Baraitser’s concept of waiting. This qualitative study employs close reading as the method of data collection, focusing on narrative passages that depict waiting, silence, and emotional restraint. Data are analysed stylistically through lexical choice, narrative tone, and patterns of emotional expression, and reported descriptively to demonstrate how meaning is constructed. The analysis shows that maternal experience is shaped through waiting, silence, restraint, and endurance rather than open emotional expression. Motherhood is framed as a moral responsibility rather than personal choice. Loss and disappointment are conveyed in controlled language, while anger and frustration are softened or omitted. Waiting functions as a narrative strategy regulating time, emotion, and the female body. These findings indicate that maternal trauma is normalised through patience and acceptance, while silence is reinforced as a socially acceptable response to suffering.